Legality and Proof of Unwritten Agreements from a Civil Law Perspective - Agustini, Shenti; Jaya, Febri; Rusdiana, Shelvi (Faculty of Law, Universitas Pattimura, 2024)
Introduction: Making agreements in Indonesia can be done in written and unwritten form. This is in accordance with the principle of freedom of contract in the Civil Code. Unwritten agreements are also very often carried out in the business world because they are more efficient. However, unwritten agreements are problematic because they are very difficult to prove in civil court.Purposes of the Research: There are 2 (two) objectives in this research, namely first, to analyze the legal strength of unwritten agreements from the perspective of civil law books and second, to analyze evidence in civil courts for cases of breach of contract in unwritten agreements. Then to find the right legal solution in resolving default problems in civil court.Methods of the Research: The research method used in this research is normative juridical. This method uses literature study techniques. The type of data used comes from primary data, namely the Civil Code and legal principles, namely freedom of contract. then the secondary legal material used is in the form of previous research articles which examine the validity of unwritten agreements.Results of the Research: Based on the research results, it was found that unwritten agreements have binding legal force. However, in reality it is very difficult to prove it in court because evidence in civil law comes from written letters. Therefore, the solution that can be offered is the need for preventive and repressive legal efforts.